Dataset on neuropsychological profile and microbiota composition in cognitively unimpaired elderly and Alzheimer's patientsMendeley Data - Luis Heredia; David Mateo; Nerea Carrión; Margarita Torrente (Data in Brief)
This article presents data collected from a total of 50 older adults (25 healthy controls and 25 diagnosed with Alzheimer's disease). Among the assessments performed in this sample was a comprehensive neurocognitive screening: including working memory, cognitive flexibility, perception, attention, motor coordination, inhibitory control, verbal fluency and visuo-spatial skills. The data presented also include analysis of the participants' gut microbiota using the shot gun approach in faecal samples. Finally, evaluations of the emotional state, level of functioning and adherence to the Mediterranean lifestyle of all participants are also available. Despite the limited sample size due to challenges in patient recruitment, present data could be useful in the identification of microbial signatures potentially predictive of cognitive decline or AD progression and also for helping to the design of clinical trials targeting the microbiome to assess effects on cognitive function. Furthermore, it is well known that the gut microbiota exhibits significant variability associated with lifestyle habits, diet, and geographic location, underscoring the critical influence of environmental and cultural factors in shaping its composition. These data are of utmost importance when considering regional and lifestyle-related diversity in microbiome research, as they can help researchers explore personalized therapeutic approaches and enhance participant stratification in future clinical trials.